Determination of lead in plastic food packaging by graphite furnace atomic absorption spectrometry - Silva, Tiago Varão [UNESP]; Miranda, Kelber [UNESP]; Ferreira, Edilene Cristina [UNESP]; Santos, Mirian Cristina [UNESP]; Neto, José Anchieta Gomes [UNESP]; Barbosa, Fernando (My University, 2015)
Lead sulfate and lead stearate are commonly used as additives or stabilizers to protect plastic material from chemical degradation. Moreover, lead Chromate is used in pigments. Considering that the presence of Pb in plastic material used for food and beverage packaging may cause deleterious effects to the human body, a simple and fast analytical method for Pb monitoring in plastic food packaging is proposed. Direct solid sampling high-resolution continuum source graphite furnace atomic absorption spectrometry (DSS HR-CS GFAAS) was used as the analytical technique and calibration against aqueous standards was employed. A mixture of Pd(NO3)2 and Mg(NO3)2 was used as the chemical modifier. The developed method was applied to different plastic containers. For comparison, some samples were also analyzed by inductively coupled plasma mass spectrometry (ICP-MS). The concentration of Pb in the evaluated samples varied from 16 to 793 μg kg-1. A paired t-test at a 95% confidence level showed that the DSS HR-CS GFAAS method provided similar results as those obtained by ICP-MS. The proposed method resulted in a characteristic mass of 5.0 pg of Pb and a limit of detection of 4.9 μg kg-1. The relative standard deviation ranged from 2.7 to 18.8% for the determinations by DSS HR-CS GFAAS and from 2.1 to 13.3% when using ICP-MS.